2006
DOI: 10.1007/s10143-006-0041-9
|View full text |Cite
|
Sign up to set email alerts
|

Central neurocytoma: two case reports and review of the literature

Abstract: Central neurocytomas are low grade tumours usually located in the lateral ventricles next to Monro foramina. This paper reviews the literature on central neurocytomas observed in the last few years and discusses their clinical, histopathological, immunohistochemical and genetic characteristics. Important correlations between therapeutic strategies and biological findings as well as new genetic discoveries are also discussed. Two illustrative cases in which the authors report preliminary results about molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 56 publications
3
17
0
Order By: Relevance
“…CNs mostly affect young adults between 20 and 40 years of age, with a peak at 30 years of age ( Fig. 1) [9]. We have observed that both genders can be equally affected, which are consistent with previous reports [14,49].…”
Section: Incidencesupporting
confidence: 88%
“…CNs mostly affect young adults between 20 and 40 years of age, with a peak at 30 years of age ( Fig. 1) [9]. We have observed that both genders can be equally affected, which are consistent with previous reports [14,49].…”
Section: Incidencesupporting
confidence: 88%
“…CN comprise 0.1-0.5% of all intracranial tumors, with only a limited number of cases reported since they were recognized as a separate pathological entity by Hassoun et al [1] in 1982 [18,19] . CN resemble oligodendrogliomas because of their appearance under light microscopy; either special staining for synaptophysin or neuron-specific enolase, or electron microscopy for neuronal ultrastructural features is required to make the diagnosis [20,21] .…”
Section: Discussionmentioning
confidence: 99%
“…There was not any mitotic activity, necrosis, pleomorphism, microvascular proliferation ( Figure 3). with in a fibrillary stroma, mimicking a neuropil [1][2][3][4]. Chromatin has usually a salt and pepper appearance.…”
Section: Image Articlementioning
confidence: 99%
“…A few cells, which probably representing entrapped astrocytic glial cells, show staining for glial fibrillary acid protein (GFAP). A typical neurocytoma is a rare variant of CN, with cellular pleomorphism, miCentral neurocytomas (CNs) are extremely rare tumors mainly seen in the 20-40 year age group with a pre dominant location in the lateral ventricles near Monro for amina, in the septum pellucidum or on the ventricle walls representing not more than 0.5%-0.7% of all intra cranial tumors [2,3]. Less than 500 cases of CNs have been described including large series [2,3] since there cognition of CNs as a separate pathological entity in 1982 [4].…”
Section: Image Articlementioning
confidence: 99%
See 1 more Smart Citation